Standard Criteria Response Mechanism of Pakistan Disaster Management Authority (PDMA) and Asian Development Bank (ADB): Evidence from Pakistan - Khattak, Shariq Riaz; Ahad, Zeeshan; Khan, Dr Muhammad Wasim Jan; Khattak, Sana Aroos (Advances in Social Sciences Research Journal, 2017)
Since the dawn of history and civilization human beings have suffered colossal losses due to natural and anthropogenic causes of various types, scales and dimensions. Floods and earthquakes of relatively recent past exposed the degree and vulnerability of Pakistan in general and Khyber Pakhtunkhwa (KPK) in particular. This study aimed to evaluate the capacity, affectivity and weakness of Pakistan Disaster Management Authority (PDMA) and compare and contrast it with the standards of Asian Development Bank (ADB). Data obtained through comprehensive questionnaires were processed through SPSS to determine the most important and least important five factors affecting disaster management in this specified region. The data analysis results of this study revealed and concluded that Pakistan Disaster Management Authority has yet to reach to a level where it is seen as a successful and effective organization that has the ability and capacity to deal with the mega disaster caused by natural and anthropogenic agents/sources.